Development of the “Bisik Lalongklek” Game to Improve Receptive Language Skills in Children Aged 4–5 Years - Alim, Rochmatul; Hasibuan, Rachma; Komalasari, Dewi; Dewi, Dwi Jayanti Kurnia (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to develop a learning medium in the form of the “Bisik Lalongklek” game to enhance the receptive language skills of children aged 4–5 years. Receptive language ability is crucial for young children to understand instructions, recognize vocabulary, and provide appropriate responses. This study employed a Research and Development (R&D) method, involving stages of problem identification, product design, expert validation, product revision, and both limited and extensive trials. The research subjects were group A children aged 4–5 years, with data collected through observation and documentation. Validation results from material and media experts indicated that the “Bisik Lalongklek” game falls within the “highly feasible” category, with an average feasibility percentage above 85%. The findings revealed that the children showed improvement in understanding instructions, recognizing vocabulary, and responding appropriately. This study demonstrates that integrating physical movement and traditional games can create enjoyable and meaningful learning experiences. The motor involvement and verbal interaction embedded in the game encourage children to be more active in processing information. Therefore, the “Bisik Lalongklek” game can serve as an innovative, educational learning medium aligned with the developmental characteristics of early childhood and can be effectively implemented by teachers in classroom learning activities.